Novel control by the CA3 region of the hippocampus on neurogenesis in the dentate gyrus of the adult rat. - Jian Xin Liu; Scarlett B Pinnock; Joe Herbert (PLoS ONE, 2011)
The dentate gyrus is a site of continued neurogenesis in the adult brain. The CA3 region of the hippocampus is the major projection area from the dentate gyrus. CA3 sends reciprocal projections back to the dentate gyrus. Does this imply that CA3 exerts some control over neurogenesis? We studied the effects of lesions of CA3 on neurogenesis in the dentate gyrus, and on the ability of fluoxetine to stimulate mitotic activity in the progenitor cells. Unilateral ibotenic-acid generated lesions were made in CA3. Four days later there was no change on the number of either BrdU or Ki67-positive progenitor cells in the dentate gyrus. However, after 15 or 28 days, there was a marked reduction in surviving BrdU-labelled cells on the lesioned side (but no change in Ki-67+ cells). pCREB or Wnt3a did not co-localise with Ki-67 but with NeuN, a marker of mature neurons. Lesions had no effect on the basal expression of either pCREB or Wnt3a. Subcutaneous fluoxetine (10 mg/kg/day) for 14 days increased the number of Ki67+ cells as expected on the control (non-lesioned) side but not on that with a CA3 lesion. Nevertheless, the expected increase in BDNF, pCREB and Wnt3a still occurred on the lesioned side following fluoxetine treatment. Fluoxetine has been reported to decrease the number of "mature" calbindin-positive cells in the dentate gyrus; we found this still occurred on the side of a CA3 lesion. We then showed that the expression GAP-43 was reduced in the dentate gyrus on the lesioned side, confirming the existence of a synaptic connection between CA3 and the dentate gyrus. These results show that CA3 has a hitherto unsuspected role in regulating neurogenesis in the dentate gyrus of the adult rat.